Construction Of Vac IV : Towards The Development Of DNA Vaccine Candidate Against Tuberculosis [RA644.T7 A284 2008 f rb]. - Said@Fauzi, Agustine Nengsih (2007)

(untitled)
Tuberculosis (TB) is the one of leading cause of death in the world, caused by a bacterium, Mycobacterium tuberculosis. The disease affects 1.7 billion people every year which is equivalent to one-third of the entire world population.